The Aerotropolis Disconnect: Airport-Led Development And Coastal Tourism Stagnation In Yogyakarta, Indonesia - Carlos Iban; Bima Andi Gunawan; Vincentius Tangguh Atyanto Nugroho (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
The coastal region of Yogyakarta, Indonesia, exemplifies a critical paradox: the rapid development of the Yogyakarta International Airport (YIA) megaproject has not produced integrated growth within the established Congot–Glagah–Trisik Regional Tourism Strategic Area. This research adopts a descriptive qualitative design to investigate this phenomenon, conceptualised as an “aerotropolis disconnect.” Methodological rigour is maintained through triangulation. Primary data were obtained via purposive sampling of 13 multi-scalar key informants from airport authorities, government, and local operators, and systematically cross-referenced with extensive field observations of physical infrastructure gaps and a longitudinal analysis of local revenue (PAD) data from 2019 to 2024. The interactive analysis model was employed to identify structural governance barriers. The findings reveal a condition of “infrastructure-induced stagnation,” wherein the capital-intensive gateway functions as a “transit bubble” that bypasses local ecosystems. This disconnect results from a structural “governance void,” characterised by fragmented planning and the absence of collaborative networks between the state-owned airport authority and the regency government. Consequently, the airport operates as a self-contained commercial entity rather than as a regional anchor. Theoretically, this research provides a novel extension to Butler’s (1980) Tourism Area Life Cycle (TALC) model by conceptualising a phase of 'Infrastructure-Induced Stagnation.' This identifies a developmental stage in which stagnation is precipitated not by traditional market saturation but by structural velocity gaps and 'enclave' dynamics created by adjacent megaprojects.